ANALYSIS OF LONG-TERM AIR TEMPERATURE TRENDS OF THE BELGRADE CENTRAL URBAN ZONE - Lukić Petrović, Milica (Bulletin of Natural Sciences Research, 2026)
This paper analyzes long-term air temperature trends in the central urban zone of Belgrade over the period 1991–2020. The research is based on a dataset obtained from the principal meteorological station Belgrade - Observatory, using daily minimum, maximum, and mean air temperature values, as well as measurements recorded at 07:00h, 14:00h, and 21:00h CET (6 different air temperature variables). Trends were examined at annual and seasonal levels as well as through the mean 30-year and mean 10-year values, for each decade of the research period (1991-2000; 2001-2010; 2011-2020) in order to identify changes in local climatic conditions within Belgrade’s densely urbanized environment. The results indicate a consistent increase in all analyzed temperature variables during the observed period. Positive trends were detected in mean daily, minimum, and maximum temperatures, as well as in seasonal and annual values, ranging from 0.064°C/year to 0.084°C/year at the annual level, and for seasons from 0.053°C/year to 0.079°C/year (spring), from 0.055°C/year to 0.084°C/year (summer), from 0.076°C/year to 0.091°C/year (autumn) and from 0.069°C/year to 0.082°C/year (winter), with the most pronounced warming occurring after 2011. The strongest increase was observed in evening temperatures (21:00 CET), especially during summer and autumn.